2016
DOI: 10.1111/pcn.12418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cognitive behavioral group therapy for recovery of self‐esteem on community‐living individuals with mental illness: Non‐randomized controlled trial

Abstract: From within-group trends and between-group differences in self-esteem, we conclude that CBGTRS may have a relatively long-term effect on self-esteem recovery. T2 is the turning point for moods and cognition; thus, follow-up is needed 3 months following the initial program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
1
16
1
1
Order By: Relevance
“…Over the course of the investigation, depressive symptoms showed a stronger linear decline for patients with higher gains in self-esteem between the first and the last measurement but the decrease was not related to initial self-esteem. The present results are thus in accordance with Kunikata et al (2016), who reported a steady increase of self-esteem along with seGBT in a sample of community-living patients.…”
Section: Discussionsupporting
confidence: 93%
“…Over the course of the investigation, depressive symptoms showed a stronger linear decline for patients with higher gains in self-esteem between the first and the last measurement but the decrease was not related to initial self-esteem. The present results are thus in accordance with Kunikata et al (2016), who reported a steady increase of self-esteem along with seGBT in a sample of community-living patients.…”
Section: Discussionsupporting
confidence: 93%
“…Promover a autoestima (Bulechek. Butcher, Dochterman, & Wagner, 2018) Encorajar o cliente a identificar as suas forças; (Bulechek et al, 2018) Reforçar as forças pessoais identificadas pelo cliente; (Bulechek et al, 2018) Encorajar o cliente a falar para si mesmo no dia a dia no sentido de verbalizar afirmações positivas; (Bulechek et al, 2018) Providenciar experiências que permitam aumentar a autonomia do cliente; (Bulechek et al, 2018) Assistir o cliente na identificação de respostas positivas por parte dos outros; (Bulechek et al, 2018) Assistir o cliente a lidar com o bullying ou as provocações; (Bulechek et al, 2018) Transmitir confiança na capacidade do cliente para lidar com a situação; (Bulechek et al, 2018) Assistir o cliente na definição de metas realistas que permitam aumentar a autoestima; (Bulechek et al, 2018) Assistir o cliente a reavaliar as perceções negativas sobre si; (Bulechek et al, 2018) Encorajar o aumento da responsabilidade por si; (Bulechek et al, 2018) Explorar sucessos prévios; (Bulechek et al, 2018) Encorajar o cliente a avaliar o seu próprio comportamento; (Bulechek et al, 2018) Encorajar o cliente a aceitar novos desafios; (Bulechek et al, 2018) Recompensar ou elogiar os progressos do cliente em direção às suas metas; (Bulechek et al, 2018) Facilitar um ambiente e o envolvimento em atividades que permitam aumentar a autoestima; (Bulechek et al, 2018;Jung et al, 2018) Realizar verbalizações positivas acerca do cliente (Bulechek et al, 2018) Providenciar apoio emocional (Ebrahimi et al, 2014) Planear [reestruturação cognitiva] (Buchanan, 2013;Johnson et al, 2013;Kunikata et al, 2016) Executar [reestruturação cognitiva] (Buchanan, 2013;Johnson et al, 2013;Kunikata et al, 2016) Assistir na [modificação] do comportamento (Buchanan, 2013;Kunikata et al, 2016) Planear [aconselhamento] (Johnson et al, 2013) Executar [aconselhamento] (Johnson et al, 2013) Planear terapia pela reminiscência…”
Section: Intervenções De Enfermagemunclassified
“…A variety of CBT techniques have been suggested for relieving death anxiety, including cognitive restructuring, graded exposure, mindfulness meditation, interpersonal skills training, and activity scheduling (Menzies and Dar-Nimrod 2017). Several recent studies have confirmed the effectiveness of CBT in strengthening the structure of anxiety buffering systems by fostering self-esteem (Kunikata et al 2016), interpersonal relationships (Song et al 2018), and symbolic immortality (Kissane et al 2004).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%